Re-examining the role of hematopoietic stem cell transplantation in relapsed large B-cell lymphoma in the era of chimeric antigen receptor (CAR) T-cell therapy - Moyo, Tamara K.; Vaidya, Rakhee (Frontiers in Oncology, 2024)
Historically, salvage chemoimmunotherapy with consolidative autologous hematopoietic stem cell transplantation (ASCT) was the only potentially curative therapeutic option for patients with relapsed/refractory large B-cell lymphoma (LBCL). Treatment options were few and outcomes poor for patients whose lymphoma failed to respond to salvage chemotherapy/ASCT and for patients not eligible for ASCT. The approval of chimeric antigen receptor (CAR) T-cell therapy for relapsed/refractory LBCL revolutionized the treatment landscape with unprecedented response rates and durability of responses. As a result, earlier intervention with CAR T-cell therapy has been explored, and the enthusiasm for CAR T-cell therapy has overshadowed ASCT. In this article, we will review the data available for ASCT and CAR T-cell therapy in relapsed LBCL and will examine the role for ASCT in relapsed/refractory LBCL in the era of CAR T-cell therapy.